Presenting a Model of Effective Factors on Successful Implementation of Descriptive Evaluation in the Primary Education System of Iran - Nabavizadeh, Seyedeh Zahra; Mashinchi, Ali Asghar; Hashemi, Seyed Ahmad; Mohammadjani, Sedigheh (Iranian Journal of Educational Sociology, 2022)
Purpose: Descriptive evaluation, if successfully implemented can play an important role in promoting the academic success and performance of elementary students. As a result, the present study was conducted with the aim of presenting a model of effective factors on successful implementation of descriptive evaluation in the primary education system of Iran. Methodology: The present study in terms of purpose was quantitative applied and in terms of implementation method was descriptive from type of quantitative. The research population was the heads and deputies of public universities, faculty members and experts of the Educational Research and Planning Institute, professors of education, doctoral students of education and faculty members and experts of the Research, Evaluation, Validation and Quality Assurance Center of Education in the 2020 year. The research sample based on Krejcie and Morgan table was estimated 178 people who were selected by stratified random sampling method with respect to job position ratio. The research instrument was a researcher-made questionnaire of effective factors on successful implementation of descriptive evaluation in the primary education system of Iran (129 items) which its content validity was confirmed by experts and its construct validity was confirmed by exploratory factor analysis method and its reliability was obtained by Cronbach's alpha method for the whole 0.89 and for factors higher than 0.70. Data were analyzed by methods of exploratory factor analysis and structural equation modeling in SPSS and Smart PLS software. Findings: Findings showed that the effective factors on successful implementation of descriptive evaluation in the primary education system of Iran have ten factors and two dimensions of manpower (including four factors of teachers' ability, motivational factors, structural factors and factors related to students) and curriculum (including six factors of multidimensional curriculum, fit of curriculum with facilities, fit of curriculum with needs of individual and community, content of curriculum, flexibility of curriculum and students' satisfaction from curriculum). Other findings showed that the model of effective factors on successful implementation of descriptive evaluation in the primary education system of Iran had a good fit and both manpower and curriculum had a direct and significant effect on it (P